The role of consultant in adoption of green building practice in response to climate change - Nurul Nabila, Abdul Latef (2014)
The construction and operation of building contribute to environmental impacts. There are existent and emerging options to improve our environment performance which are called as green building practices. Green building significantly can reduce environmental impact. The main organization promoting building techniques and green practices in Malaysia is the Standards and Industrial Research Institute of Malaysia (SIRIM). However, they are now put in a new rating system called Green Building Index (GBI). The GBI rating system provides a huge number of opportunities for developers to construct and design sustainable building. Green building brings advantages to social, economic and environmental aspect. However, one of the challenges in widespread Green Building practices is finding person that are knowledgeable to implement green design in the project. Thus, there is important for consultants that have a great knowledge to play their role in widespread Green Building practice. Objectives in this research are to determine the responsibilities and the role of consultant in increasing the use of Green Building, to determine the consultant's primary barriers in increasing green building practice and to suggest strategies in lowering those barriers in order to encourage consultant to adopt more environmentally responsible practices. The data presented in this thesis are derived from both interviewer and responses to a questionnaire that completed by. consultant. The role as Green Building consultant only can be play if there is need from the client. Hence, the consultants have to take chance to always advice or suggest client to implement GBI in their project. The major barriers are Green Building design is too expensive, the lack of expressed interest from client and the lack of training and education in Green Building design. Hence, a few suggestions had been discussed in order to lower the barriers which are educate our community about the important of Green Building practices, expand the opportunities of professional training and education in sustainable practices and government should provide economic incentives for sustainable building project.